PENGUNGGAHAN KEMBALI KONTEN TANPA IZIN UNTUK KEPENTINGAN KOMERSIAL DI INSTAGRAM DITINJAU DARI UU NO. 28 TAHUN 2014 TENTANG HAK CIPTA - Hanifa (2023)
The activity of re-post video content by repost accounts is rife on various social media, one of which is Instagram. On social media Instagram, there are not a few repost accounts that re-post video content without permission without including the name of the content creator and these accounts are then used to gain commercial interests through paid promotion services. Departing from this phenomenon, this study aims to find out the regulations regarding re-posting of content without permission that is used for commercial purposes on Instagram based on Law No. 28 of 2014 concerning Copyright, and to find out the role of government oversight of acts of re-posting content without permission and used for commercial purposes on Instagram. The preparation of this research uses a normative juridical research method with a statutory approach and a case approach. The results of this study state that the activity of re-posting video content without permission without including the name of the creator and used for commercial purposes on Instagram is a copyright infringement which can cause legal consequences in the form of sanctions for compensation claims as stipulated in Article 99 of the Copyright Law, or sanctions for criminal charges as stipulated in article 113 paragraph (3) of the Copyright Law. The government also has a supervisory role for internet media-based content based on Article 54 of the Copyright Law. The government, in this case DJKI, implements this supervisory role through close control with the issuance of Joint Ministerial Regulations Number 14 of 2015 and Number 26 of 2015 concerning Implementation of Closing Content and/or User Access Rights for Copyright Infringement and/or Related Rights in Electronic Systems. Keywords: Copyright, Content, Re-post